2002
DOI: 10.2105/ajph.92.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-Based Surveys of Adolescent Risk-Taking Behaviors: Reducing the Bias of Absenteeism

Abstract: Guttmacher et al. | Peer Reviewed | Research and Practice | 235 RESEARCH AND PRACTICE  Objectives. This investigation examined the effectiveness of intensive efforts to include frequently absent students in order to reduce bias in classroom-based studies.Methods. Grade 10 students in 13 New York City high schools (n = 2049) completed self-administered confidential surveys in 4 different phases: a 1-day classroom capture, a 1-day follow-up, and 2 separate 1-week follow-ups. Financial incentives were offered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…Students who are truant also often exhibit risk behaviors, such as substance abuse, school disconnection, sexual activity, and violence (Barry et al, 2011;Guttmacher, Weitzman, Kapadia, & Weinberg, 2002). These risk behaviors were not reported in the interviews but deserve further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Students who are truant also often exhibit risk behaviors, such as substance abuse, school disconnection, sexual activity, and violence (Barry et al, 2011;Guttmacher, Weitzman, Kapadia, & Weinberg, 2002). These risk behaviors were not reported in the interviews but deserve further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…While it is unclear how these students would have responded to the survey, other data (not shown) from this survey do show a relationship between absence from school for nonmedical reasons and club drug use. Previous research on the impact of student absenteeism on adolescent risk-taking has shown that absent students have either similar or higher rates of risk behavior than nonabsent students (Guttmacher et al, 2002). Therefore, the results observed with participating students may be considered as conservative estimates of club drug use and school behaviors in this population.…”
Section: Discussionmentioning
confidence: 96%
“…Assessment of effects of absenteeism on adolescent reports of health behaviors has shown it may be a problem. 55 Students in alternative schools are excluded from the sample and have been shown to have higher levels of health-related risk behaviors than high school students surveyed in the Centers for Disease Control and Prevention's Youth Risk Behavior Survey. 56 Thus, the levels of risk reported here may be lower than those of the adolescent population as a whole.…”
Section: Commentmentioning
confidence: 99%